Better arthritis care: Patients' expectations and priorities, the competencies that community‐based health professionals need to improve their care of people with arthritis?. (21st July 2017) - Erwin, J.; Edwards, K.; Woolf, A.; Whitcombe, S.; Kilty, S.
Abstract: Objective: The aim of the present study was to identify the competencies that patients think non‐specialist community‐based nurses and allied health professionals (AHPs) need to enable them to assess, care for and manage arthritis appropriately. Methods: Four face‐to‐face focus groups were held with a total of 16 women and nine men with arthritis, to discuss the care they received from community‐based health professionals, the skills and knowledge they expected from community‐based health professionals and what they prioritized. Results: People with arthritis wanted health providers to have an understanding of the difference between inflammatory arthritis (IA) and osteoarthritis (OA), of how serious OA can be, and of the unpredictability of IA and flares. They emphasized the need for nurses and AHPs to understand the psychosocial impact of arthritis on individuals, family and friends, and the psychological adjustment needed when diagnosed with IA. They wanted community‐based health professionals to have some knowledge of the types of drug treatments that people with IA receive and the implications of taking immunosuppressive drugs. They also wanted them to understand the pain associated with arthritis, particularly OA, which participants felt was not taken seriously enough. They wanted nurses and AHPs in the community to be able to give basic advice on pacing and pain management, to make multidisciplinary referrals, to communicate effectively between referral points and to be able to signpost people to sources of help and good, reliable sources of education and information (especially for OA). They also wanted them to understand that patients who have had a diagnosis for a long time are the experts in their own disease. Other areas which were emphasized as being important were good communication skills and taking a holistic approach to caring for people with arthritis. Conclusions: OA and IA differ significantly, both in their nature and their management. However, patients with arthritis want health professionals working in the community to be able to take a holistic approach to arthritis, with an understanding not just of the physical effects, but also their impact on the lives of patients, their family and their wider social circle, and on their ability to participate. People with OA want their condition to be taken seriously and to be offered appropriate management options, while people with IA want professionals to understand the unpredictability of their condition and to have a basic understanding of the drugs used for its treatment.